Enhancing Diagnostic Accuracy with AI : A Review of Current Applications and Future Directions - Chandra Sagili, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines the transformative impact of artificial intelligence on healthcare diagnostics, focusing on current applications, implementation strategies, and future directions. The article encompasses various domains, including medical imaging, pathology, and genomics, where AI has significantly improved diagnostic accuracy and efficiency. The article explores healthcare institutions' integration challenges, including technical barriers, clinical adoption hurdles, and regulatory considerations. Through extensive analysis of multi-institutional data, this review highlights successful implementation frameworks, quality assurance protocols, and emerging technological trends. The findings underscore the potential of AI to enhance healthcare delivery while maintaining high standards of patient care, particularly in resource-constrained settings. By synthesizing evidence from diverse healthcare environments, this review provides valuable insights for healthcare providers, administrators, and policymakers navigating the complex landscape of AI integration in clinical practice.
Keywords: Artificial Intelligence in Healthcare; Diagnostic Accuracy Enhancement; Clinical Integration Frameworks; Medical Imaging Analytics; Healthcare Implementation Challenges